Nosocomial person-to-person transmission of severe fever with thrombocytopenia syndrome. (May 2019) - Jung, I.Y.; Choi, W.; Kim, J.; Wang, E.; Park, S.-W.; Lee, W.-J.; Choi, J.Y.; Kim, H.Y.; Uh, Y.; Kim, Y.K.
Abstract: Objectives: This study is an epidemiologic investigation of nosocomial severe fever with thrombocytopenia syndrome virus (SFTSV) transmission among healthcare workers (HCWs) after contact with an index patient. The aim of this study was to determine whether exposure to blood or bloody respiratory secretion is associated with human-to-human transmission of SFTSV. Methods: Eleven days after the index patient died, two HCWs who had close exposure to the patient presented with typical symptoms of SFTS. An epidemiological investigation was conducted on all 25 HCWs who had been in close contact with the index patient. Clinical and laboratory data were collected, and transmission rate before and after the index patient had haemorrhagic manifestations was analysed. Results: Among 25 HCWs who had direct contact with the index patient, five HCWs were confirmed to have SFTS. All five HCWs had contact to blood or bloody respiratory secretions of the index patient without adequate use of personal protective equipment (PPE). No HCW with contact before haemorrhagic manifestations of the index patient contracted SFTS. Overall, the transmission rate was higher for HCWs who had contact after the index patient had haemorrhagic manifestations (33.3%, five of 15 HCWs, vs. 0%, zero of ten HCWs, p 0.041). Conclusions: In HCWs who are inadequately protected, person-to-person transmission of SFTSV may be associated with contact with blood or bloody respiratory secretions. Therefore, universal precaution and full PPE is highly recommended for protection against SFTSV when there are signs of bleeding.